2019
DOI: 10.1088/2053-1591/ab572c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PVA/Chitosan samples by electrospinning and film casting methods and evaluating the effect of surface morphology on their antibacterial behavior

Abstract: Chitosan due to outstanding properties including biocompatibility, biodegradability, nontoxicity and antibacterial activity has received considerable attention in different fields of biomedical engineering.To study the effect of morphology and topology on antibacterial activity of chitosan, two samples of PVA/Chitosan blend with the same concentration and volume ratio were prepared using electrospinning and film casting methods. To improve the electrospinability of chitosan, it was hydrolyzed by 50% V NaOH sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…According to the results of Table 1 and Figure 12, coated scaffolds (sample B) against E. coli appear to have superior antibacterial effects in comparison with S. aureus after 24h. This is in consistent with the findings of our previous study [36] as well as results reported in other studies [43][44][45]. It seems that the high hydrophilicity of Gram-negative bacteria in comparison with Gram-positive species renders them more susceptible to the membrane damage via chitosan cations.…”
Section: Discussionsupporting
confidence: 93%
“…According to the results of Table 1 and Figure 12, coated scaffolds (sample B) against E. coli appear to have superior antibacterial effects in comparison with S. aureus after 24h. This is in consistent with the findings of our previous study [36] as well as results reported in other studies [43][44][45]. It seems that the high hydrophilicity of Gram-negative bacteria in comparison with Gram-positive species renders them more susceptible to the membrane damage via chitosan cations.…”
Section: Discussionsupporting
confidence: 93%
“…The parameters frequently used to measure surface roughness are, Rp; maximum height Rz; arithmetic mean height, Ra; and root mean square height, Rq. The surface roughness can influence the type of bacteria and the amount of bacteria that adhere to the surfaces [ 164 ]. Apart from roughness, the wettability of surfaces also can affect the bacterial growth and biofilm development on surfaces.…”
Section: Characterization Antibacterial Polymer Materialsmentioning
confidence: 99%
“…Chitosan-based nanofibers were utilized for wound dressing, bone scaffold, and ligands for epithelial cells. There are studies in the literature on chitosan-based nanofibers for wound dressing, bone scaffold, ligands for epithelial cells as a mixture of synthetic polymers such as polyethylene oxide (PEO), polyamide (PA6), PCL, and PVA (Alhosseini et al 2012;Charernsriwilaiwat et al 2014;Mendes et al 2016;Kuntzler et al 2018;Nokhasteh et al 2019).…”
Section: Polymer Used In Nanofiber Fabricationmentioning
confidence: 99%